Effects of developmental stages, sex difference, and diet types of the host marmalade hoverfly (Episyrphus balteatus) on symbiotic bacteria - Wang, Xiaoyun; Huangfu, Ningbo; Chen, Lulu; Zhang, Kaixin; Li, Dongyang; Gao, Xueke; Li, Bingbing; Wang, Li; Zhu, Xiangzhen; Ji, Jichao; Luo, Junyu; Cui, Jinjie (Frontiers in Microbiology, 2024)
Introduction Symbiotic bacteria play key roles in a variety of important life processes of insects such as development, reproduction and environmental adaptation, and the elucidation of symbiont population structure and dynamics is crucial for revealing the underlying regulatory mechanisms. The marmalade hoverfly (Episyrphus balteatus) is not only a remarkable aphid predator, but also a worldwide pollinator second to honeybees. However, its symbiont composition and dynamics remain unclear. Methods Herein, we investigate the symbiotic bacterial dynamics in marmalade hoverfly throughout whole life cycle, across two sexes, and in its prey Megoura crassicauda by 16S rRNA sequencing. Results In general, the dominant phyla were Proteobacteria and Firmicutes, and the dominant genera were Serratia and Wolbachia. Serratia mainly existed in the larval stage of hoverfly with the highest relative abundance of 86.24% in the 1st instar larvae. Wolbachia was found in adults and eggs with the highest relative abundance of 62.80% in eggs. Significant difference in species diversity was observed between the adults feeding on pollen and larvae feeding on M. crassicauda, in which the dominant symbiotic bacteria were Asaia and Serratia, respectively. However, between two sexes, the symbionts exhibited high similarity in species composition. In addition, our results suggested that E. balteatus obtainded Serratia mainly through horizontal transmission by feeding on prey aphids, whereas it acquired Wolbachia mainly through intergeneration vertical transmission. Taken together, our study revealed the effects of development stages, diet types and genders of E. balteatus on symbionts, and explored transmission modes of dominant bacteria Serratia and Wolbachia. Discussion Our findings lay a foundation for further studying the roles of symbiotic bacteria in E. balteatus life cycle, which will benefit for revealing the co-adaptation mechanisms of insects and symbiotic bacteria.